Emerging Trends in Information System Security Using AI & Data Science for Next-Generation Cyber Analytics - Rehman, Faisal; Khan, Inam Ullah; Arshi, Oroos; Gupta, Shashi Kant (Information Systems Engineering and Management, 2025)
XIV, 203 p. 56 illus., 51 illus. in color.